Desarrollo del turismo de naturaleza en la reserva ecológica Varahicacos - Tejeda Montero, M. T.; Rodríguez Reina, M. V.; Vega Vázquez, H.; Núñez Mora, J. C.; Finalé, J. E. (Geographicalia, 2016)
In this work are offered the knowledge and experiences on the mechanisms and action courses that should be impelled so that the nature tourim in the Ecological Reservation Varahicacos is constituted in compatible benefit with the primary objectives of conservation and satisfaction of current demand of this type of tourism. It is the summary of the results of the investigations and set in practices of the methodology of the geoecological design, which takes, as theoretical and practical basis, the experience of other countries and the cubana reality, and uses the advanced techniques as basic tools (Remote Sensing, Digital Cartography and Geograpliical Information Systems) .